(untitled) (International Journal of Engineering and Computer Science, 2017)
Mobile ad hoc networks (MANET) represent complex distributed systems that comprise wireless mobile nodes that can freely and dynamically self organize into arbitrary and temporary ad hoc network topologies. A mobile ad hoc network is a collection of nodes that is connected through a wireless medium forming rapidly changing topologies. The widely accepted existing routing protocols designed to accommodate the needs of such self-organized networks do not address possible threats aiming at the disruption of the protocol itself. In this paper In this paper, we compare we compare and evaluate the performance metrics Ad-hoc On-demand Distance Vector (AODV) routing protocol, Ad-hoc On-demand Multipath Distance Vector (AOMDV) routing protocol. This paper investigates all these routing protocols corresponding to packet delivery fraction (pdf), end to end delay, Packet loss. The ns-2 simulation results showed that AODV has better performance compare to AOMDV routing protocol mobile ad-hoc network.